Understanding and quality of minimum competency assessment (AKM) questions made by Integrated Science teachers in junior high schools - Ernawati, Ernawati; Manik, Fatkul Yudhistira; Trisnawati, Ratna Dwi; Emiliana, Emiliana; Yuliawati, Sri (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
The main problem with implementing the minimum competency assessment (Asesmen Kompetensi Minimum or AKM) is the teacher's lack of understanding of AKM. The assessment questions made by the teacher are still limited to testing memory. The level of variation and difficulty of the questions presented is also still low (LOTS), contrary to the government's expectation to improve the quality of learning outcomes which are oriented toward students' higher-order thinking stages (HOTS). This research employed a mixed method. An overview of the teacher's understanding was obtained through questionnaires and interviews, while the description of the quality of the AKM of Integrated Science items made by the teacher was analyzed using the item quality rubric based on Bloom's taxonomy. The data source was obtained from 25 Integrated Science teachers for class VIII of junior high school in Bekasi City. The data were collected through three stages. The first stage employed the Google Form survey to see the demographic map of informants and teachers' initial understanding of AKM. In the second stage, five informants were selected from the results of the survey, representing the data source's characteristics. Then, in the third stage, literature analysis was done to develop rubric criteria for assessing the quality of AKM items. This rubric was used by the research team to assess the quality of AKM items made by an Integrated Science teacher at a junior high school in Bekasi City. Questions that meet the criteria for good questions were collected and entered into the AKM question bank.